Contribuições ao estudo de fungos Agaricomycetes Briófilos no Rio Grande do Sul, Brasil - Lopes , Cassiane Furlan (2025)
The order Basidiomycota is the second most species-rich among fungi, with the class Agaricomycetes alone comprising more than 30,000 described species, including edible, toxic, and ecologically diverse species (saprophytic, lichenized, bryophilous, parasitic, among others). Bryophilous fungi, which grow in association with bryophytes, are still poorly studied, and in Brazil, studies addressing the ecology of these organisms and their associations, as well as those analyzing their taxonomy, are scarce. Therefore, this study aims to estimate the diversity of Agaricomycetes fungi, especially those of the order Agaricales in association with bryophytes (Bryophyta and Marchantiophyta), in the riparian forest of the Rio dos Sinos, located in the Floresta Nacional de São Francisco de Paula, in the state of Rio Grande do Sul, Brazil, contributing to the understanding of their ecological associations. To this end, bibliographic reviews were conducted based on searches in platforms such as Google Scholar, Scielo, NCBI, among other databases. Field collections employed the walking method along the trails of the Floresta Nacional de São Francisco de Paula, where basidiomata exhibiting growth associated with bryophytes were collected. This material was subsequently analyzed by optical microscopy, photographed, and oven-dried for storage. Taxonomic regions of the fungi and bryophytes, as well as evidence of associations between these organisms, such as hyphae at the periphery or within the cellular layer of the bryophytes, were analyzed. For molecular data analysis, extraction, amplification, and sequencing of the LSU region were performed, and for phylogenetic analysis, Bayesian inference, maximum likelihood, and maximum parsimony methods were used. In the first chapter, the review addressed only bryophilous Agaricales from Brazil, identifying 19 species and producing an identification key, of which nine are recognized as moss parasites. In the second chapter, the bibliographic review was expanded to the entire class Agaricomycetes, where 33 species were catalogued, belonging to Agaricales, Boletales, Hymenochaetales, and Polyporales. In the third chapter, novel microscopic associations between fungi and bryophytes were described, such as Gerronema stuckertii with Campylopus pilifer, Galerina stylifera with Campylopus julicaulis and Chlorella sp., Oudemansiella platensis with Metzgeria consanguinea, and Psathyrella murrilli with Brachythecium sp. In the fourth chapter, the association of Rimbachia bryophila, which is a new record for Brazil, with Dicranella riograndensis, Neesioscyphus argillaceus, and Jungermannia decolor was described. In the fifth chapter, we described morphologically and phylogenetically, with molecular characters, Cora simasi Furlan-Lopes & Putzke, associated with Neesioscyphus argillaceus, Campylopus uleanus, and Dicranella riograndensis. The phylogenetic analysis placed C. simasi in the subclade Applanata, close to C. applanata, and revealed a sister-group relationship between the Ciferrii and Aspera lineages. All bryophilous fungal species were evidenced by hyphae distributed in the bryophytes studied without evident parasitic structures, suggesting a non-harmful relationship. It was observed that the diversification of Cora is influenced by geographical and environmental isolation, with adaptations to humid, high-altitude microhabitats.